A genome–wide CRISPR activation screen identifies SCREEM a novel SNAI1 super-enhancer demarcated by eRNAs - Dinesh Babu Uthaya Kumar; Dinesh Babu Uthaya Kumar; Marina Yurieva; Jessica Grassmann; Lina Kozhaya; Caleb Dante McBride; Derya Unutmaz; Adam Williams; Adam Williams; Adam Williams (Frontiers in Molecular Biosciences, 2023)
The genome is pervasively transcribed to produce a vast array of non-coding RNAs (ncRNAs). Long non-coding RNAs (lncRNAs) are transcripts of >200 nucleotides and are best known for their ability to regulate gene expression. Enhancer RNAs (eRNAs) are subclass of lncRNAs that are synthesized from enhancer regions and have also been shown to coordinate gene expression. The biological function and significance of most lncRNAs and eRNAs remain to be determined. Epithelial to mesenchymal transition (EMT) is a ubiquitous cellular process that occurs during cellular migration, homeostasis, fibrosis, and cancer-cell metastasis. EMT-transcription factors, such as SNAI1 induce a complex transcriptional program that coordinates the morphological and molecular changes associated with EMT. Such complex transcriptional programs are often subject to coordination by networks of ncRNAs and thus can be leveraged to identify novel functional ncRNA loci. Here, using a genome-wide CRISPR activation (CRISPRa) screen targeting ∼10,000 lncRNA loci we identified ncRNA loci that could either promote or attenuate EMT. We discovered a novel locus that we named SCREEM (SNAI1 cis-regulatory eRNAs expressed in monocytes). The SCREEM locus contained a cluster of eRNAs that when activated using CRISPRa induced expression of the neighboring gene SNAI1, driving concomitant EMT. However, the SCREEM eRNA transcripts themselves appeared dispensable for the induction of SNAI1 expression. Interestingly, the SCREEM eRNAs and SNAI1 were co-expressed in activated monocytes, where the SCREEM locus demarcated a monocyte-specific super-enhancer. These findings suggest a potential role for SNAI1 in monocytes. Exploration of the SCREEM-SNAI axis could reveal novel aspects of monocyte biology.